Baltimore or, the steadfast tin soldier and the vampire - Mignola, Michael 1960-; Golden, Christopher 1967- (Dark Horse Books, 2015)
Infected by a demonic vampire while fighting in the Ardennes forest during World War I, Lord Henry Baltimore summons three friends and prepares himself for a final showdown with the Red King